POLYMORPHISM OF SIMPLE SEQUENCE REPEAT REGIONS OF SULAWESI EBONY (DIOSPHYROS CELEBICA BAKH.) IN EXPERIMENTAL FOREST OF HASANUDDIN UNIVERSITY PROVENANCE - Siti Halimah Larekeng; Muh. Restu; Gusmiaty Gusmiaty; Rismawati Rismawati (Universitas Sembilanbelas November Kolaka, 2016)
Polymerase Chain Reaction (PCR)-based molecular techniques have been used to detect the polymorphism in plants. The utilization of molecular markers plays essential role in germplasm characterization and plant breeding since the information of DNA marker technology can be exchanged between laboratories and should have standard method to be reproducible. The molecular aspect has been commonly linked to DNA isolation protocol and polymorphic molecular marker, thus can be used for molecular research recommendation purposes. The objectives of this study were to evaluate the capability of microsatellite marker of Ebenaceae Family for amplifying Ebony DNA, and to determine the appropriate PCR annealing temperatures. The DNA isolation of Ebony leaves from Experimental Forest of Hasanuddin University Provenance was carried out using Genomic DNA Mini Kit (Plant) Geneaid protocol. Nine of seventeen selected primers from the Genus Diospyros were able to amplify Ebony DNA. Amplification products produced polymorphic bands with different annealing temperatures (ranged from 53 to 56°C). These nine polymorphic primers will be recommended to use for future studies in genetic diversity as well as pollen dispersal pattern analyses.